Evaluating system performance in Gigabit networks - Salah, K. (2003)
With the current wide deployment of Gigabit Ethernet technology in the backbone and workgroup switches, the network performance bottleneck has shifted for the first time in nearly a decade from the network to the end hosts and servers. This dramatic bandwidth increase calls for optimizations and good design considerations in many key components of the hosts and servers. These key components include network adaptor, operating system, protocol stack, memory, and processing power. More importantly the high bandwidth increase can negatively impact the OS performance due to the interrupt overhead caused by the incoming Gigabit traffic. This paper presents models and analytical techniques for studying such a negative impact. We first present an analytical model for the ideal system when interrupt overhead is ignored. We then present two models which describe the impact of high interrupt rate on system throughput. One model is for network adaptors not equipped with DMA engines, and the other model is for network adaptors equipped with DMA engines. In addition we study the system performance when using different system delivery options of packet data to user applications. Results from both simulations and reported experimental findings show that our analytical models are valid and give a good approximation.